PERSEPSI DOSEN TERHADAP PENGEMBANGAN PEMBELAJARAN DILEMA ETIKA UNTUK MAHASISWA PROGRAM STUDI SARJANA KEDOKTERAN FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Liegangsaputro, Elizabeth Thalia; Darmayani, I Gusti Ayu Sri; Putra Manuaba, Ida Bagus Amertha; Sundariyanti, I Gusti Ayu Harry (Essence of Scientific Medical Journal; Vol 22 No 2 (2025): Volume 22 No. 2 (November 2024 - Maret 2025) Essential: Essence of Scientific Medical Journal, 2025)
Introduction: Ethical dilemmas in the doctor-patient context refer to situations where individuals face two or more choices that contain conflicting moral values. Many doctors feel confused and lack confidence when making decisions related to ethical dilemmas. Therefore, it is crucial to teach ethical dilemmas from an early stage. This study aims to explore approaches to learning about ethical dilemmas, focusing on relevant learning objectives, teaching methods, and assessment methods suitable for implementation at Udayana University for preclinical medical students. Method: The research design employed is explorative qualitative research, with data collection techniques involving in-depth interviews. The study sample consists of four faculty members from the Medical Study Program at the Faculty of Medicine, Udayana University. Result: The findings highlight the importance of implementing this learning for preclinical students at Udayana University to help them sharpen their understanding and skills in dealing with situations involving ethical dilemmas. Discussion: Recommended learning methods, such as role play and problem-based learning, can be effectively integrated to improve students' comprehension of medical ethics. Additionally, the easiest assessment method to incorporate into the curriculum is multiple-choice questions. However, it is suggested that assessments should not only focus on theoretical aspects but also consider students' mindsets, such as essay evaluations and video role play presentations. Conclusion: To effectively integrate learning about ethical dilemmas, it is essential to carefully select learning objectives, teaching methods, and assessment methods. This will ensure that the learning process proceeds smoothly and achieves the desired outcomes. Keywords: curriculum, ethical dilemmas, ethics education, medical students